2020
DOI: 10.1242/jcs.239939
|View full text |Cite
|
Sign up to set email alerts
|

Increased host ATP efflux and its conversion to extracellular adenosine is crucial for establishing Leishmania infection

Abstract: Intracellular survival of Leishmania donovani demands rapid production of host ATP for its sustenance. However, a gradual decrease in intracellular ATP in spite of increased glycolysis suggests ATP efflux during infection. Accordingly, upon infection, we show here that ATP is exported and the major exporter was pannexin-1, leading to raised extracellular ATP levels. Extracellular ATP shows a gradual decrease after the initial increase, and analysis of cell surface ATP-degrading enzymes revealed induction of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 84 publications
2
13
0
Order By: Relevance
“…The expression of CD73 in resident peritoneal macrophages has been described in the previous studies [40,41]; however, to the best of our knowledge, no previous study has evaluated the expression of this enzyme after an extended period of incubation such as the one used in the present study. During infection, macrophages secrete ATP via pannexin channels [42][43][44] or P2X7 receptors [45]. Accumulation of Resident macrophages were obtained from naïve mice by injecting 10 ml of ice-cold PBS into the peritoneal cavity and rested for 72 h at 37 °C.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of CD73 in resident peritoneal macrophages has been described in the previous studies [40,41]; however, to the best of our knowledge, no previous study has evaluated the expression of this enzyme after an extended period of incubation such as the one used in the present study. During infection, macrophages secrete ATP via pannexin channels [42][43][44] or P2X7 receptors [45]. Accumulation of Resident macrophages were obtained from naïve mice by injecting 10 ml of ice-cold PBS into the peritoneal cavity and rested for 72 h at 37 °C.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that ATP induces PAD2 activity via P2X7 receptors (25). While ATP is required for almost all biological reactions as the universal energy source (115), once host cells are damaged, stressed, or infected by pathogens, intracellular ATP can be released to become extracellular ATP which serves as a key "danger" signaling molecule (116)(117)(118). Additionally, certain pathogens can also produce and secrete extracellular ATP (119,120).…”
Section: Infections Sepsismentioning
confidence: 99%
“…15,76 How AMPK is activated in Leishmania-infected macrophages remains unclear. Leishmania infection can lead to the efflux of ATP, 77 which would alter intracellular pools of AMP/adenosine diphosphate/ATP and potentially activate AMPK in the host cell. The released ATP is converted to adenosine by the surfaceexpressed ectonucleotidases, CD39/CD73 and adenosine deaminase (ADA2), leading to the activation of G-protein receptors, A 2A R and A 2B R, which have also been shown to promote M2 polarization.…”
Section: Ampk Signaling Also Modulates Leishmania Growthmentioning
confidence: 99%
“…The released ATP is converted to adenosine by the surfaceexpressed ectonucleotidases, CD39/CD73 and adenosine deaminase (ADA2), leading to the activation of G-protein receptors, A 2A R and A 2B R, which have also been shown to promote M2 polarization. 77 AMPK can also be activated by cytoplasmic galectins that detect lysosomal damage, 78 although whether Leishmania amastigotes activate this pathway is unknown. More broadly, it remains unclear whether visceralizing Leishmania species simultaneously activate both AMPK and mTORC1 signaling pathways to their advantage.…”
Section: Ampk Signaling Also Modulates Leishmania Growthmentioning
confidence: 99%
See 1 more Smart Citation